Intelligent and Secure Package Receiver System Utilizing Internet of Things (IoT) Technology - Retno Dwi Handayani; Zaidir Jamal; M. Alkahfiansyah; Lia Rosmalia; Novi H. Sudibyo; Riko Herwanto (Universitas Negeri Surabaya or The State University of Surabaya, 2025)
The rapid expansion of e-commerce has increased the demand for secure and efficient package delivery solutions, particularly for recipients who are frequently away from home. This study presents the development of a Smart Package Receiver Box, an Internet of Things (IoT)-based system that integrates sensors and remote control functionalities to enhance package security. The system incorporates an ESP32-CAM microcontroller, an ultrasonic sensor for courier detection, a PIR sensor for package counting, and a solenoid door lock for secure access control. These components are integrated with the Telegram messaging application, enabling real-time notifications, visual monitoring, and remote control of package deliveries. Experimental testing demonstrates that the system reliably detects couriers within a 5 cm to 30 cm range, accurately counts inserted packages, and ensures a secure locking mechanism with prompt response times. The collected data confirm stable system performance, minimal delays, and effective remote accessibility for users. Despite its advantages, the system presents certain limitations that warrant further improvements. The current implementation lacks encrypted communication, posing potential security vulnerabilities that could be mitigated by integrating AES-256 encryption and secure authentication protocols. Additionally, the system's reliance on Telegram makes it susceptible to disruptions in service availability, necessitating the incorporation of alternative communication channels such as SMS notifications or cloud-based APIs. Future enhancements will focus on strengthening data security, increasing system redundancy, and conducting comprehensive field testing to improve robustness and scalability for broader adoption in modern package delivery systems.